The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1186/s13104-015-1515-z
|View full text |Cite
|
Sign up to set email alerts
|

Depression among people with epilepsy in Northwest Ethiopia: a cross-sectional institution based study

Abstract: BackgroundEpilepsy is the world’s most common neurological disorder, affecting approximately 50 million people worldwide and contributed to different psychiatric illness. Depression is one of the most frequent co morbid psychiatric disorders that affects the life of the patients’. This study aimed to assess the prevalence of depression and associated factors among epileptic patients attending the outpatient department of the University of Gondar Hospital, Northwest Ethiopia, 2014.MethodsInstitution based quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
62
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 25 publications
(41 reference statements)
23
62
5
1
Order By: Relevance
“…19 One explanation might be the method of diagnosis, which may lead to different reported occur- Most studies show that individuals with a lower level of education are more likely to suffer from anxiety and depression. 6,23 However, this study fails to support the association between education, depression, and anxiety. This may result from the small number of highly educated patients in this population, thereby not providing enough power to demonstrate any differences.…”
Section: Discussioncontrasting
confidence: 73%
“…19 One explanation might be the method of diagnosis, which may lead to different reported occur- Most studies show that individuals with a lower level of education are more likely to suffer from anxiety and depression. 6,23 However, this study fails to support the association between education, depression, and anxiety. This may result from the small number of highly educated patients in this population, thereby not providing enough power to demonstrate any differences.…”
Section: Discussioncontrasting
confidence: 73%
“…The prevalence of depression among PWE in this resource limited setting using the primary care validated cut-off (70.8%) was also higher than the general population depression prevalence (28.8%) using the same validated cut-off (5 or more) [38]. This prevalence of depression was also higher than the prevalence that is reported in the institution based studies from Ethiopia [79]. Various explanations have been proposed to explain the elevated levels of depression in epilepsy; (1) underlying structural brain disease, (2) damage related to uncontrolled seizures, and (3) psychosocial impact of the stigma and disability associated with epilepsy [6].…”
Section: Discussionmentioning
confidence: 77%
“…Hospital based studies conducted in Ethiopia have shown that the prevalence of depression is high among people with epilepsy [79]. Comorbid psychiatric disorders, such as depression, have a substantial negative impact on quality of life [1012] and are important risk factors for suicidal behaviours [13].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Bifftu et al [57] conducted a cross-sectional study of 405 epileptics and found that patients who could not read and write, and those who had primary education and secondary education were 8 times, 6 times and 4 times more likely to have depression than those with college education, respectively.…”
Section: Other Factorsmentioning
confidence: 99%